Genius. The complete second season, Picasso [videorecording (DVD)] - Banderas, Antonio; Poésy, Clémence; Rich, Alex; Colley, Samantha, 1979- (20th Century Fox Home Entertainment, 2018)
"'Genius: Picasso' is the second season of National Geographic's first fully scripted drama series. Diving into the life and loves of the brilliant Spanish artist Pablo Picasso ... this season showcases Picasso's significant and wide-ranging contribution to modern art. Exploring the Spanish expatriate's devotion to his craft, the series also reveals Picasso's relationships with other well-known personalities of the time, including Coco Chanel, Henri Matisse, Marc Chagall and Jean Cocteau. From the younger Picasso ... who rejects academic study and joins a circle of young, struggling bohemian artists and writers in early 20th century Spain and France, to the artist's tumultuous marriages, passionate affairs and ever-shifting political and personal alliances, 'Genius: Picasso' uncovers what sparked Picasso's creative drive and pushed his artistic boundaries leading to his worldwide renown as a genius."--